The Role of Interleukin-6 Inhibitors in the Treatment of COVID-19 Infections: A Case Series - Tadepalli, Satish (Cureus, 2020)
An outbreak of severe acute respiratory distress syndrome coronavirus 2 (SARS-CoV-2) infection started in December 2019 in China that resulted in a global health emergency. The World Health Organization later named the disease as coronavirus disease 2019 (COVID-19). Currently, there is no effective treatment available and the data are evolving through continuous clinical trials and ongoing research. Severe infections present with hypoxemic respiratory failure from acute respiratory distress syndrome as one of the major complications. We report two cases of COVID-19 patients who initially presented with moderate to severe symptoms. Later, their clinical course worsened despite ongoing treatment with multiple medications such as hydroxychloroquine and azithromycin until they were started on tocilizumab. Within a short period after they were administered tocilizumab, their oxygen saturation improved and other inflammatory markers such as D-dimer levels, lactate dehydrogenase, and ferritin levels decreased. There is an increase in the amount of research citing the role of various cytokines in the pathophysiology of COVID-19. Targeting the inflammatory mediators in the pathogenesis, especially interleukin-6 pathway inhibitors, would improve overall morbidity and mortality, thus decreasing the burden on healthcare systems.